Subcutaneous entomophthoramycosis in a healthy 9-year-old boy - Oberdorfer, Peninnah; Phloenchaiwanit, Piti; Kongthavonsakul, Kritsana; Chaiwun, Benjaporn (Biomedical Sciences and Clinical Medicine, 2024)
Pediatric entomophthoramycosis is an uncommon disease. We reported a case of a healthy 9-yearold boy with a subcutaneous mass under his right eyebrow. The mass was 2 x 1 cm in size and had no signs of inflammation. The patient had neither previous underlying diseases nor trauma. A histopathologic examination of the mass revealed eosinophilic granulomas and broad ribbon like hyphae, which are characteristic of entomophthoramycosis. After 6-weeks treatment with trimethoprim-sulfamethoxazole and itraconazole, the soft tissue mass decreased in size and disappeared.